Classification of small-scale farmers for improved rainfall variability management in South Africa. Issue 1 (2nd January 2020) - Mkuhlani, Siyabusa; Crespo, Olivier; Rusere, Farirai; Zhou, Leocadia; Francis, Joseph
ABSTRACT: Adoption of research-based rainfall variability management strategies among small-scale farmers in South Africa is limited. A study was therefore conducted to improve understanding of rainfall variability management using the farm typology, and snowball and focus group discussion approaches. Farmers across all categories highlighted experiencing changing climate patterns. Resource-constrained farmers utilized non-finance demanding strategies like mulch. Mixed farming households utilized crop and livestock-based strategies such as manure. All farmers highlighted inadequate funding as a challenge. Enterprising pensioners and horticulture-dependent farmers cited lack of climate information as an impediment. Combining this knowledge with seasonal forecast information potentially results in improved climate variability management.